2020
DOI: 10.1002/etc.4660
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Bioaccumulation Across Trophic Levels and Along a Longitudinal Gradient in Headwater Streams

Abstract: Toxic effects of selenium (Se) contamination in freshwaters have been well documented. However, study of Se contamination has focused on lentic and larger order lotic systems, whereas headwater streams have received little scrutiny. In central Appalachia, surface coal mining is a common Se source to headwater streams, thus providing a useful system to investigate Se bioaccumulation in headwater food chains and possible longitudinal patterns in Se concentrations. Toward that end, we assessed Se bioaccumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
4
10
0
Order By: Relevance
“…Similarly to Se distribution, Se bioaccumulation in BMI taxa was greater at sites with higher Se exposure (Sites 1, 2, and 4), a trend also reported by others (Cianciolo et al, 2020;Muscatello & Janz, 2009;Orr et al, 2006). At these sites, Se concentrations in some BMI taxa (e.g., caddisflies, chironomids, dragonfly nymphs, and gastropods) exceeded the selected benchmark of 4 µg/g dry weight (BCMoE, 2014) and were comparable to the lower range of Se concentration data for chironomids (9.4-87.9 µg/g dry wt) and predatory BMI taxa (8.7-94 µg/ g dry wt) sampled from other uranium mine-influenced lakes in northern Saskatchewan (Muscatello et al, 2008;Wiramanaden et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly to Se distribution, Se bioaccumulation in BMI taxa was greater at sites with higher Se exposure (Sites 1, 2, and 4), a trend also reported by others (Cianciolo et al, 2020;Muscatello & Janz, 2009;Orr et al, 2006). At these sites, Se concentrations in some BMI taxa (e.g., caddisflies, chironomids, dragonfly nymphs, and gastropods) exceeded the selected benchmark of 4 µg/g dry weight (BCMoE, 2014) and were comparable to the lower range of Se concentration data for chironomids (9.4-87.9 µg/g dry wt) and predatory BMI taxa (8.7-94 µg/ g dry wt) sampled from other uranium mine-influenced lakes in northern Saskatchewan (Muscatello et al, 2008;Wiramanaden et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…At these sites, Se concentrations in periphyton were comparable to those observed to reduce fecundity and survival of mayflies, genus Centroptilum (Conley et al, 2009(Conley et al, , 2014, sampled in Vulture Lake. Selenium enrichment in periphyton was at the same order of magnitude as reported in the literature for sites receiving continuous Se input (Arnold et al, 2017;Cianciolo et al, 2020). Furthermore, and as other studies indicated (DeForest et al, 2007;Graves et al, 2019a;Markwart et al, 2019;Whitmore et al, 2018), greater Se enrichment in periphyton was observed at sites with relatively low aqueous Se concentrations, such as Sites 6 and 10 (reference); and inversely, lower enrichment was observed in Vulture Lake and at Site 4, near the diluted effluent diffuser.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Fine‐sedimentation was, unexpectedly, not a prominent stressor, and relationships between habitat and reproductive guilds were counterintuitive. Our results are consistent with studies highlighting the influence of mining‐impacted stream production on biotic assemblages (Cianciolo et al., 2020; Northington et al., 2011; Presser, 2013; Voss & Bernhardt, 2017; Whitmore et al., 2018) and emphasise the complexity of mining impacts manifest through novel species‐ and trait‐based sensitivities paired with water and habitat quality alterations.…”
Section: Discussionsupporting
confidence: 92%
“…Correlations between water column trace element concentrations and those in fish in other studies are variable (Anatone et al 2020;Cianciolo et al 2020;Donadt et al 2021). Bioavailability of a trace element is partially dependent on the state it occurs in.…”
Section: Discussionmentioning
confidence: 95%